2018
DOI: 10.5505/tjtes.2018.68473
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effects of Thalidomide and Etanercept on Septic Rats Exposed to Lipopolysaccharide

Abstract: BACKGROUND:The aim of this study was to evaluate the therapeutic effects of thalidomide and etanercept on lipopolysaccharide (LPS)-induced sepsis in a rat model. METHODS:Thirty male Wistar Albino rats were divided into 5 groups: Control, LPS, LPS+Thalidomide, LPS+Etanercept, and LPS+Thalidomide+Etanercept. The control group was given a 1 mL intraperitoneal (i.p.) injection of 0.9% saline solution. For endotoxic treatment, the rats were injected with a single i.p. dose of LPS (Escherichia coli 0111:B4 (5 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Hence, great effort was made to develop potent inhibitors targeting cytokines like TNF‐α, IL‐1, and IL‐6 or their corresponding receptors leading to the generation of highly specific and effective clinically validated compounds like etanercept, anakinra, and tocilizumab [134]. Based on their efficacy in preclinical sepsis models, great hope has been placed in these small molecular inhibitors and antagonistic monoclonal antibodies [135–138]. However, none of them did add significant benefit for the treatment of sepsis or septic shock in clinical trials.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Hence, great effort was made to develop potent inhibitors targeting cytokines like TNF‐α, IL‐1, and IL‐6 or their corresponding receptors leading to the generation of highly specific and effective clinically validated compounds like etanercept, anakinra, and tocilizumab [134]. Based on their efficacy in preclinical sepsis models, great hope has been placed in these small molecular inhibitors and antagonistic monoclonal antibodies [135–138]. However, none of them did add significant benefit for the treatment of sepsis or septic shock in clinical trials.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Ilhan et al found that the administration of thalidomide and etanercept as therapeutic agents resulted in a significant decrease in the level of TNF-α 32 . Ilhan et al conducted an experimental study with etanercept in septic rats and found that serum MDA level significantly decreased following an etanercept treatment 33 . In line with these findings, our results showed that etanercept significantly reduced inflammatory and oxidative stress parameters in sepsis.…”
Section: /7mentioning
confidence: 99%
“…Damage to the stomach increases the levels of various proinflammatory cytokines, triggering the recruitment of leukocytes that stimulate inflammatory responses 5 . Tumor necrosis factor-α (TNF-α) stimulates the transcription of inflammatory mediator cytokines such as interleukin-6 (IL-6) and IL-1β 6,7 .…”
Section: Introductionmentioning
confidence: 99%